Total Anomalous Pulmonary Venous Connection: Preoperative Anatomy, Physiology, Imaging, and Interventional Management of Postoperative Pulmonary Venous Obstruction. (June 2017) - Files, Matthew D.; Morray, Brian
Total anomalous pulmonary venous connection refers to a spectrum of cardiac anomalies where the pulmonary veins fail to return to the left atrium and the pulmonary venous blood returns through a systemic vein or directly to the right atrium. There is a wide anatomical variety of venous connections and degrees of pulmonary venous obstruction that affect the presentation, surgical repair, and outcomes. In this review, we explore the preoperative physiology, echocardiographic diagnosis, and approach to postoperative complications.